EKSPLORASI KEANEKARAGAMAN BURUNG SEBAGAI DAYA TARIK UTAMA AVITOURISM DI EKOWISATA MANGROVE CUKU NYINYI, KABUPATEN PESAWARAN - Putri Maharani, Nafa; Budi Yuwono, Slamet; Iswandaru, Dian; Prayitno Harianto, Sugeng (Universitas Pattimura, 2024)
Birds play a significant ecological role and are also attractive for birdwatching tourism (avitourism), particularly in mangrove ecosystems which provide habitat and food sources. Exploring the avian diversity in the Cuku NyiNyi Mangrove Ecotourism Area for avitourism development can be a conservation effort for birds and provide economic incentives for local communities. This study aimed to identify bird species as potential attractions for avitourism in the Cuku NyiNyi Mangrove Ecotourism Area. Data analysis involved determining the conservation status and criteria of birds as potential objects and attractions for avitourism. A total of 32 bird species from 19 families were identified with a total of 113 individuals. Several bird species have conservation statuses that require attention, namely the cinnamon-headed green pigeon (Treron fulvicollis) which is categorized as vulnerable (VU) and the brahminy kite (Haliastur indus), crested serpent eagle (Spilornis cheela), racket-tailed treepie (Crypsirina temia), and malaysian pied fantail (Rhipidura javanica) which are protected species. The analysis showed that 18 bird species have the potential to be objects and attractions for avitourism based on criteria such as raptors, protected species, songbirds, endemic birds, and colorful birds. The avian diversity in the Cuku NyiNyi Mangrove Ecotourism Area supports the potential for avitourism to develop as a form of sustainable tourism for the protection of bird species while attracting tourists, especially birdwatchers.